Sustainability Prize 4 Back to the future: Re-introducing Reusable gowns to achieve #NetZeroSurgery. (9th August 2022) - Beatty, Jasmine Winter; Gan, Jonathan; Robb, Henry; Dryden, Simon; Ortega, Patricia; Purkayastha, Sanjay
Abstract: Aims: In view of the planetary health emergency, we aimed to introduce an efficient and safe intervention to rapidly decrease the environmental impact of our surgical department whilst delivering financial and social benefits. Methods: The project was registered with the Audit and Quality Improvement Department. Carbon hotspot identification and process mapping were performed. A survey of theatre staff members was completed prior to the trial to ensure agreement. Disposable surgical gowns were replaced with reusable gowns in two theatres. Where appropriate, reinforced gowns were substituted with standard gowns. Staff were notified and posters made to remind them of correct removal procedures. Environmental savings were estimated using published figures (Vozzola et al. 2018) and weights. Trust procurement data from 2019 was used to estimate financial and environmental savings. Staff evaluations were collected. Preliminary results were shared with heads of surgical specialties, surgical managers, A&E, ITU and Anaesthesia across the trust. Results: 97.7% (74/77) of staff were favourable to trying the reusable gowns prior to the trial. 91.3% (42/46) gave positive feedback after testing them clinically and 97.8% (45/46) were happy to continue using them again. 3051 gowns were substituted over 6 months, leading to a saving of 3.292 tonnesCo2e. Savings were estimated at £366 from reductions in waste disposal and standard gown use. Conclusions: Approval has been gained to extend the trial across the trust and a business proposal is being considered. Scaled to the whole trust this intervention could save 234.7 tonnesCO2e/year, equivalent to driving a car around the equator 23.6 times.